Taxonomic Status of Stingless Bee Lepidotrigona Arcifera (Hymenoptera: Meliponini) From The Southwest China - Tibetan Plateau - Yao, Yuxin; Tang, Xiangyou; Li, Yaohui; Song, Huali; Jiang, Yan; Chen, Xinlan; Zha, Luo; Wang, Wenfeng; Xu, Jinshan (Journal of Apicultural Science, 2024)
The stingless bee, , which was first reported in northeast India is a pollinating insect of the tropical and subtropical regions of the world. However, little information about this species is known in terms of taxonomic status as well as detailed morphological characteristics. In this study, we discovered a stingless bee in Tibet that belongs to an Alpine climate region. The morphological comparison with the India stingless bee, confirms that this newly discovered species is from the Tibet plateau. To determine the taxonomic status of this Tibetan stingless bee, we sequenced the 16S rRNA and COI genes of samples from a dozen colonies and compared them to some other known bee species. Phylogenetic analysis shows that Tibetan is grouped with the other stingless bee species and most closely sistered to the stingless bee, . The genetic distance between Tibetan and the other stingless bee species is approaching those between pairwise bee species belonging to other such bee genera as and . Hence, our results not only offer new information on species distribution and morphological characteristics of but also confirm its taxonomic status among stingless bees for the first time, which will contribute to understanding the biodiversity of stingless bees in the future.